Positive electrode diaphragm and preparation method and application thereof
By introducing a fibrous three-dimensional structure and a bridging structure into the positive electrode film in the dry electrode, the problem of uneven dispersion of conductive agent was solved, and the low resistivity and high conductivity of the electrode were achieved, thus improving the overall performance of sodium-ion batteries.
Patent Information
- Application Number
- CN202511346518.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-19
- Publication Date
- 2025-12-09
AI Technical Summary
In dry electrode technology, uneven dispersion of conductive agents leads to high electrode resistivity, which limits charge and discharge efficiency and rate performance, hindering applications in high-power scenarios.
The positive electrode membrane is composed of positive electrode active material, solid electrolyte, conductive agent, polytetrafluoroethylene and polyvinylidene fluoride. Through the fibrous three-dimensional structure and bridging structure, the conductive agent and solid electrolyte are uniformly dispersed, forming a continuous electron transport path and ion transport channel, thereby reducing the electrode resistivity.
It effectively reduces electrode resistivity, improves electrode conductivity, enhances film formation and mechanical strength, and is suitable for large-scale commercial applications of sodium-ion batteries.
Smart Images

Figure CN121097015A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of dry process technology, and in particular to a positive electrode film, its preparation method, and its application. Background Technology
[0002] Amid the global energy transition, sodium-ion batteries (SIBs) have emerged as a highly promising energy storage solution due to their abundant material resources, low cost, and long lifespan. Their application prospects in fields such as electric vehicles, renewable energy storage, and portable devices have attracted much attention.
[0003] Cathode materials are crucial to the performance of sodium-ion batteries. Currently, they mainly include layered transition metal oxides (such as NaCoO2 and NaNiO2), phosphate materials (such as NaFePO4), and polyanionic materials. To achieve high-performance sodium-ion batteries, cathode material preparation must balance high electrochemical performance, production process feasibility, and cost-effectiveness to meet the demands of large-scale commercial applications.
[0004] The manufacturing process of the positive electrode directly affects the battery's energy density, power density, cycle stability, and safety. Although the traditional wet coating process is widely used, it relies on solvents and suffers from problems such as solvent evaporation, high energy consumption, environmental pollution, and low production efficiency.
[0005] With technological advancements, dry electrode technology has emerged as a potential alternative process. It eliminates the need for solvents, avoiding the energy-intensive wet drying process and the emission of volatile organic compounds (VOCs), offering advantages in both environmental friendliness and cost control. The principle involves physically mixing the cathode material and binder, then using compression molding technology to create thin-film electrodes. This improves production efficiency, reduces energy consumption, and increases electrode compaction density, thereby enhancing battery energy density.
[0006] However, the dry process faces challenges, such as uneven dispersion of conductive agents and high electrode resistivity, which limit charge and discharge efficiency and rate performance, hindering applications in high-power scenarios.
[0007] In summary, the environmentally friendly and low-cost advantages of dry electrodes conflict with the stringent requirements for conductivity in electrode materials. Therefore, reducing the resistivity and improving the conductivity of the electrode are key technical issues in dry electrode research. Summary of the Invention
[0008] The purpose of this invention is to address the deficiencies of existing technologies by providing a positive electrode film, its preparation method, and its application. The positive electrode film provided by this invention includes a positive electrode active material, a solid electrolyte, a conductive agent, polytetrafluoroethylene (PTFE), and polyvinylidene fluoride (PVDF). Through the synergistic effect of the components, the resistivity of the electrode is reduced.
[0009] To achieve the above objectives, in a first aspect, the present invention provides a positive electrode membrane, the positive electrode membrane comprising a positive electrode active material, a solid electrolyte, a conductive agent, polytetrafluoroethylene, and polyvinylidene fluoride in a mass ratio of 84-92.5:2.5-5:3-5:1-4:1-2;
[0010] During processing, the polytetrafluoroethylene undergoes fibrosis to form nanofibers. These nanofibers interact with the positive electrode active material, the solid electrolyte, and the conductive agent through van der Waals forces, forming a physical encapsulation. Through the interweaving of the nanofibers, the positive electrode active material, the solid electrolyte, and the conductive agent are "woven" into a fibrous three-dimensional structure. This allows the conductive agent to be uniformly dispersed in the fibrous three-dimensional structure, forming a continuous electron transport path, and the solid electrolyte to be uniformly dispersed in the fibrous three-dimensional structure, forming a continuous ion transport channel, thereby reducing the resistivity of the electrode.
[0011] The polyvinylidene fluoride (PVDF) molecular chain contains -CF2-CH2- repeating units, wherein the -CF2- groups in the molecular chain provide polarity, allowing the molecular chain to simultaneously adsorb the positive electrode active material, the solid electrolyte, and the conductive agent, forming a bridging structure of "conductive agent-positive electrode active material-conductive agent" and "solid electrolyte-positive electrode active material-solid electrolyte". This allows the positive electrode active material, the solid electrolyte, and the conductive agent to form a three-dimensional network structure, ensuring that the conductive agent and the solid electrolyte are uniformly dispersed in the positive electrode active material, forming continuous electron transport paths and ion transport channels, respectively, further reducing the resistivity of the electrode.
[0012] The -CH2- groups in the polyvinylidene fluoride (PVDF) molecular chain impart flexibility to the chain. During the preparation of the positive electrode membrane, the molecular chain undergoes local segment deformation to fill the gaps between the positive electrode active material, the conductive agent, and the solid electrolyte particles. Simultaneously, under pressure, the molecular chain aligns along the pressure direction to form a dynamic "flow layer" that fills the particle gaps. The local segment deformation provides the basis for the formation of the "flow layer." Through the synergistic effect of local segment deformation and the "flow layer," the positive electrode membrane maintains structural uniformity and stability during the forming process, thereby achieving the film-forming properties of the positive electrode membrane.
[0013] Preferably, the positive electrode active material is a layered transition metal oxide, including one or more of NaCoO2 and NaNiO2;
[0014] The solid electrolyte includes one or more of sodium bis(oxalateborate), sodium bis(trifluoromethanesulfonylimide), and sodium difluorooxalateborate.
[0015] The conductive agent includes one or more of carbon nanotubes, conductive carbon black, Ketjen black, carbon fiber, and acetylene black.
[0016] In a second aspect, the present invention provides a method for preparing the positive electrode film described in the first aspect above, the method comprising:
[0017] Solid electrolyte powder was ball-milled to obtain nanoscale solid electrolyte materials;
[0018] The positive electrode active material, the solid electrolyte material, and the conductive agent are mixed evenly in a high-speed shearing machine to obtain a first mixture;
[0019] While maintaining stirring at 80℃-85℃, polytetrafluoroethylene and polyvinylidene fluoride are added to the first mixture, causing the polytetrafluoroethylene to fibrose under shear force and temperature, resulting in a second mixture with a fibrous three-dimensional structure.
[0020] The second mixture is pressed into a film using a film-forming and thinning device to obtain a positive electrode film;
[0021] In the positive electrode membrane, the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent, the polytetrafluoroethylene, and the polyvinylidene fluoride is 84-92.5:2.5-5:3-5:1-4:1-2.
[0022] Preferably, the positive electrode active material is a layered transition metal oxide, including one or more of NaCoO2 and NaNiO2;
[0023] The solid electrolyte includes one or more of sodium bis(oxalateborate), sodium bis(trifluoromethanesulfonylimide), and sodium difluorooxalateborate.
[0024] The conductive agent includes one or more of carbon nanotubes, conductive carbon black, Ketjen black, carbon fiber, and acetylene black.
[0025] Preferably, the ball milling speed is 1000rpm-3000rpm, and the ball milling time is 3h-7h.
[0026] Preferably, when preparing the first mixture, the high-speed shear machine operates at a speed of 300 rpm to 700 rpm, a time of 15 min to 25 min, and a temperature of 15°C to 20°C.
[0027] Preferably, during fiberization, the high-speed shearing machine rotates at 1000 rpm to 3000 rpm for 15 min to 25 min.
[0028] Thirdly, the present invention provides a positive electrode sheet, which includes the positive electrode film described in the first aspect above, or includes the positive electrode film prepared by the preparation method described in the second aspect above.
[0029] Fourthly, the present invention provides an energy storage device, the energy storage device comprising: for sodium-ion batteries or sodium-ion capacitors;
[0030] The energy storage device includes the positive electrode film described in the first aspect above, or the positive electrode film prepared by the preparation method described in the second aspect above, or the positive electrode sheet described in the third aspect above.
[0031] The positive electrode film provided by this invention, through the synergistic effect of its components, not only reduces the resistivity of the electrode sheet but also improves the film-forming properties of the positive electrode film.
[0032] On the one hand, polytetrafluoroethylene (PTFE) constructs a fibrous three-dimensional structure through fiberization, allowing the conductive agent and solid electrolyte to be uniformly distributed within the fibrous three-dimensional structure, forming continuous electron transport paths and ion transport channels, respectively, thus reducing the resistivity of the electrode sheet. On the other hand, due to the polarity of the -CF2- groups in the polyvinylidene fluoride (PVDF) molecular chain, the molecular chain adsorbs various components, forming a bridging structure, which in turn constitutes a three-dimensional network structure. This allows the conductive agent and solid electrolyte to be uniformly distributed within the three-dimensional network structure, forming continuous electron transport paths and ion transport channels, respectively, further reducing the resistivity of the electrode sheet.
[0033] On the other hand, the flexible CH2- groups in the polyvinylidene fluoride (PVDF) molecular chain allow the molecular chain to fill the gaps between the positive electrode active material, conductive agent, and solid electrolyte particles through local chain segment deformation during the preparation of the positive electrode film. Simultaneously, under pressure, the molecular chain aligns along the pressure direction to form a dynamic "flow layer" that fills the gaps between particles. The local chain segment deformation provides the basis for the formation of the "flow layer." Through the synergistic effect of local chain segment deformation and the flow layer, the positive electrode film maintains structural uniformity and stability during the forming process, thereby achieving the film-forming properties of the positive electrode film.
[0034] Therefore, the flexibility and long molecular chain structure of polyvinylidene fluoride endow it with good plasticity, allowing the components to adhere better together and improving the film-forming properties of the membrane. At the same time, the entanglement and interaction between the long molecular chains form cohesive forces, enhancing the overall strength of the membrane.
[0035] In summary, polytetrafluoroethylene (PTFE) constructs a fibrous three-dimensional structure, providing mechanical support and transport channels for the membrane. Meanwhile, the flexibility of polyvinylidene fluoride (PVDF) can alleviate the stress concentration that may occur during the fibrosis process of PTFE, preventing particle breakage or impact, and indirectly promoting the uniform dispersion of each component. At the same time, it complements the fibrosis of PTFE. The molecular chains of PVDF can penetrate into the micropores of the particles, filling the gaps between particles, achieving the film-forming properties of the membrane, and enhancing the adhesion strength.
[0036] The positive electrode film provided in this invention effectively solves the problem of high resistivity of existing electrode sheets, improves the conductivity of the electrode sheets, and lays a solid foundation for the large-scale commercial application of sodium-ion batteries and sodium-ion capacitors. Attached Figure Description
[0037] Figure 1 This is a schematic flowchart of a method for preparing a positive electrode film according to an embodiment of the present invention;
[0038] Figure 2 This is a winding diagram of the positive electrode film prepared in Example 1 of the present invention;
[0039] Figure 3 This is a winding diagram of the positive electrode film prepared in Comparative Example 1 of the present invention;
[0040] Figure 4 This is a winding diagram of the positive electrode film prepared in Comparative Example 2 of the present invention. Detailed Implementation
[0041] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0042] The reagents and materials used in the following examples and comparative examples are all commercially available conventional reagent products, or can be prepared by conventional methods. Where specific experimental steps or conditions are not specified in the examples, they were performed according to conventional experimental steps and conditions in the art. Unless otherwise specified, all equipment used is conventional equipment currently available in the art.
[0043] This invention provides a positive electrode membrane comprising a positive electrode active material, a solid electrolyte, a conductive agent, polytetrafluoroethylene, and polyvinylidene fluoride in a mass ratio of 84-92.5:2.5-5:3-5:1-4:1-2;
[0044] During processing, polytetrafluoroethylene (PTFE) undergoes fibrosis to form nanofibers. These nanofibers interact with the positive electrode active material, solid electrolyte, and conductive agent through van der Waals forces, forming a physical encapsulation. Through the interweaving of the nanofibers, the positive electrode active material, solid electrolyte, and conductive agent are "woven" into a fibrous three-dimensional structure. This allows the conductive agent and solid electrolyte to be uniformly dispersed in the fibrous three-dimensional structure, forming continuous electron transport paths and ion transport channels, respectively, thereby reducing the resistivity of the electrode.
[0045] Polyvinylidene fluoride (PVDF) contains repeating -CF2-CH2- units in its molecular chain. The -CF2- groups in the molecular chain provide polarity, allowing the molecular chain to simultaneously adsorb the positive electrode active material, solid electrolyte, and conductive agent, forming a bridging structure of "conductive agent-positive electrode active material-conductive agent" and "solid electrolyte-positive electrode active material-solid electrolyte". This bridging structure acts like a "bridge" between the positive electrode active material particles, connecting the dispersed particles. As the bridging mechanism continues to form and expand, the positive electrode active material, solid electrolyte, and conductive agent gradually form a three-dimensional network structure, allowing the conductive agent and solid electrolyte to be uniformly dispersed in the positive electrode active material, forming continuous electron transport paths and ion transport channels, respectively, further improving the resistivity of the electrode.
[0046] Furthermore, the -CH2- groups in the polytetrafluoroethylene (PTFE) molecular chain endow it with flexibility. During the preparation of the positive electrode membrane, when the molecular chain is under stress, localized chain segment deformation fills the gaps between the positive electrode active material, conductive agent, and solid electrolyte particles, providing a foundation for subsequent membrane structural stability. Simultaneously, under pressure, the molecular chains align along the pressure direction, forming a dynamic "flow layer." This "flow layer" further fills the interparticle gaps, reducing particle agglomeration. Because the "flow layer" acts as a lubricant and dispersant between particles, it helps improve the uniformity and stability of the membrane, thereby achieving good film-forming properties. In other words, localized chain segment deformation filling the interparticle gaps provides the basis for the formation of the "flow layer." Through the synergistic effect of localized chain segment deformation and the "flow layer," the positive electrode membrane maintains structural uniformity and stability during the forming process, thus achieving good film-forming properties.
[0047] As described above, the positive electrode active material, solid electrolyte, and conductive agent gradually form a three-dimensional network structure. This network structure significantly increases the contact area and interaction points between particles, allowing the originally dispersed particles to connect through bridging structures, thus significantly enhancing the binding force between particles. Due to the increased binding force, the relative movement between particles is restricted, thereby reducing the gaps between them. A film formation refers to a film that maintains a uniform and stable structure during the molding process, possessing good mechanical and electrochemical properties. The enhanced binding force between particles and the reduced gaps between particles make it easier for the film to maintain structural uniformity and stability during molding. Therefore, during compression molding, films with smaller particle gaps are more easily compacted, forming a dense structure, thus reducing defects such as cracking and delamination, and resulting in a complete and dense film structure. Simultaneously, the favorable three-dimensional network structure also provides the film with better mechanical strength, enabling it to withstand certain external forces and improving film-forming properties.
[0048] In addition, PVDF can improve the compactness of membranes, mainly due to the synergistic effect of polar groups (-CF2-) and flexible groups (-CH2-) in its molecular chain, which is achieved through the following mechanism:
[0049] First, the polar adsorption of the -CH2- group forms a "molecular glue" that tightly binds the positive electrode active material, conductive agent, and solid electrolyte, constructing a stable three-dimensional network structure, reducing the space for free movement of particles, resulting in a high initial packing density of the membrane, and laying the foundation for densification.
[0050] Secondly, under pressure, the -CH2- groups actively fill the tiny gaps between particles through reversible deformations such as local chain segment bending and twisting, ensuring that the membrane is densified while maintaining flexibility.
[0051] Finally, under continuous pressure, the PVDF molecular chains align and form a dynamic "flow layer" along the pressure direction, allowing the particles to rearrange, eliminate agglomeration, and further fill the remaining gaps through molecular chain sliding and recombination, thereby improving the degree of densification.
[0052] In summary, polar groups ensure the stability of the membrane structure, while flexible groups optimize particle distribution. The synergy between the two enables the membrane to maintain efficient electron / ion transport during densification, avoiding performance degradation and ultimately achieving a balance between high densification and functional integrity.
[0053] In this invention, the positive electrode active material is a layered transition metal oxide, including one or more of NaCoO2 and NaNiO2.
[0054] Solid electrolytes include one or more of sodium bis(oxalateborate)borate (NaBOB), sodium bis(trifluoromethanesulfonylimide) (NaTFSI), and sodium difluorooxalateborate (NaDFOB).
[0055] Conductive agents include one or more of carbon nanotubes, conductive carbon black, Ketjen black, carbon fiber, and acetylene black. Conductive carbon materials such as carbon nanotubes, conductive carbon black, Ketjen black, carbon fiber, or acetylene black have different morphologies and conductive properties. When used in combination or individually, they can form effective conductive pathways in electrode materials, promoting rapid electron transport and thus improving the conductivity of the electrode.
[0056] The positive electrode film in this invention utilizes the synergistic effect between its components to achieve a synergistic improvement in film formation and resistivity. The excellent film formation effect ensures the structural stability and consistency of the positive electrode sheet, providing a foundation for the long-term stable operation of the battery. Meanwhile, the lower resistivity improves the battery's charge and discharge efficiency, reduces energy loss, and helps to improve the overall performance of the battery. These comprehensive performance improvements give sodium-ion batteries using the positive electrode film prepared by this invention a greater advantage in the market and enable them to meet the battery performance requirements of more application scenarios.
[0057] The positive electrode film provided in this invention effectively solves the problem of high resistivity of films prepared by existing dry processes, improves the mechanical and electrical properties of the electrode sheet, and thus enhances the overall performance of sodium-ion batteries, laying a solid foundation for the large-scale commercial application of sodium-ion batteries and sodium-ion capacitors.
[0058] For membranes, appropriate areal density is a core parameter for balancing performance, offering advantages such as optimized electrochemical performance and improved structural stability. Specifically, if the areal density is too high, the membrane thickness increases, particles become more densely packed, and porosity decreases. This may lead to difficulties in electrolyte wetting, affecting ion transport efficiency. Furthermore, excessively high areal density increases membrane brittleness, making it prone to cracking during winding or charge / discharge processes. Conversely, low areal density results in a thinner membrane with increased porosity, allowing for more thorough electrolyte penetration, but may lead to a looser structure due to weakened interparticle bonding. Preferably, the areal density of the positive electrode membrane in this application is 20 g / cm³. 2 -30g / cm 2 .
[0059] In addition, this application also provides a method for preparing the above-mentioned positive electrode film, the main steps of which are as follows: Figure 1 As shown, it includes the following steps:
[0060] Step 110: Ball mill the solid electrolyte powder to obtain nanoscale solid electrolyte material.
[0061] By refining solid electrolyte powder to the nanoscale through ball milling, its dispersibility and activity are enhanced, and the diffusion path of ions in the electrolyte can be significantly shortened.
[0062] Furthermore, nanoscale solid electrolyte materials have high surface energy, increasing the contact area with the positive electrode active material and conductive agent, which allows for the formation of a more stable solid electrolyte interface film. When applied in batteries, this effectively suppresses the side effects of electrolyte decomposition and reduces gas generation. Preferably, the solid electrolyte includes one or more of NaBOB, NaTFSI, and NaDFOB.
[0063] Specifically, the D50 range of the ball-milled solid electrolyte material is 50nm-200nm. To prevent the solid electrolyte from getting damp and oxidizing, ball milling and dispersion can be carried out in a highly sealed container under conditions not exceeding 40°C and humidity not exceeding 1%. The ball-to-material ratio during ball milling is controlled at 10-20:1, the ball milling speed is 1000rpm-3000rpm, and the ball milling time is 3h-7h.
[0064] Step 120: The positive electrode active material, solid electrolyte material and conductive agent are mixed evenly in a high-speed shearing machine to obtain the first mixture.
[0065] The mass ratio of positive electrode active material, solid electrolyte, conductive agent, polytetrafluoroethylene and polyvinylidene fluoride is 84-92.5:2.5-5:3-5:1-4:1-2.
[0066] Specifically, the positive electrode active material is a layered transition metal oxide, including one or more of NaCoO2 and NaNiO2.
[0067] Conductive agents include one or more of carbon nanotubes, conductive carbon black, Ketjen black, carbon fiber, and acetylene black.
[0068] Shear force can achieve nano-dispersion of the mixture, avoiding local agglomeration and forming a uniform conductive network. However, if the rotation speed is too high, excessive shearing can damage the material structure, while if the rotation speed is too low, insufficient dispersion of the components will lead to local agglomeration. Appropriate mixing time can ensure sufficient contact between the components. Low temperature control can prevent premature fiberization of polytetrafluoroethylene, prevent the first mixture from clumping, and ensure process stability.
[0069] Appropriate rotation speed and time can ensure that the components are fully mixed, while avoiding material structure damage due to excessive shearing. Suitable temperature helps maintain the stability of the material and provides a guarantee for the subsequent preparation of high-performance positive electrode films. Therefore, preferably, in this step, the rotation speed of the high-speed shearing machine is 300rpm-700rpm, the time is 15min-25min, and the temperature is 15℃-20℃.
[0070] Step 130: While maintaining stirring at 80℃-85℃, polytetrafluoroethylene and polyvinylidene fluoride are added to the first mixture, causing the polytetrafluoroethylene to fibroinate under shear force and temperature, resulting in a second mixture with a fibrous three-dimensional structure.
[0071] Polytetrafluoroethylene (PTFE) possesses extremely strong molecular entanglement capabilities. Under certain temperature and shear force conditions, PTFE undergoes fibrosis, forming nanofibers. These fibers interact with the positive electrode active material, conductive agent, and solid electrolyte particles through van der Waals forces, forming physical encapsulations. Through the interweaving of the nanofibers, the positive electrode active material, conductive agent, and solid electrolyte are "woven" into a fibrous three-dimensional network structure. This allows the conductive agent to be uniformly dispersed within the fibrous three-dimensional structure, forming continuous electron transport paths, and also allows the solid electrolyte to be uniformly dispersed within the fibrous three-dimensional structure, forming continuous ion transport channels, effectively reducing the resistivity of the electrode sheet.
[0072] The fibrous three-dimensional structure has high tensile strength, which can withstand the volume expansion of the battery during charging and discharging, prevent the conductive network from breaking, and provide mechanical support.
[0073] During the fiberization process, the stirring speed needs to be moderate to prevent the polytetrafluoroethylene (PTFE) fibers from agglomerating around the high-speed shearing machine due to centrifugal force, or from failing to form a fibrous three-dimensional structure due to insufficient shear force. Furthermore, the fiberization time should not be too long, otherwise the PTFE may deorient or thermally decompose, leading to carbonization defects. If the fiberization time is too short, the uniformity of the PTFE fibers will deteriorate. Preferably, in this step, the stirring speed is 1000 rpm-3000 rpm, which provides sufficient shear force to orient and stretch the PTFE molecular chains, forming a fibrous three-dimensional structure; the stirring time is 15 min-25 min to ensure sufficient fiberization; and the temperature is 80℃-85℃, which promotes the movement of PTFE molecules and the formation of nanofibers, thereby enhancing the bonding effect with other components.
[0074] Specifically, heating the first mixture to 80℃-85℃ and adding polytetrafluoroethylene (PTFE) while stirring creates a second mixture with a specific structure. This is because the molecular chains of PTFE soften at certain temperatures. When shear force is applied to PTFE, the molecular chains slip, causing crystal deformation and the formation of nanofibers. This slippage process is similar to "chain slip," where the molecular chains slide along parallel directions rather than breaking, thus maintaining the integrity of the fiber structure. The fibrous PTFE interacts with the positive electrode active material, conductive agent, and solid electrolyte through van der Waals forces, forming a physical encapsulation. The nanofibers intertwine, "weaving" the particles into a fibrous three-dimensional structure, allowing the particles to be uniformly dispersed within it. The conductive agent, uniformly dispersed within the fibrous three-dimensional structure, forms continuous electron transport paths, while the nanoscale solid electrolyte particles, uniformly dispersed within the fibrous three-dimensional structure, form continuous ion transport channels. This reduces the resistivity of the electrode and improves the battery's rate performance and charge / discharge efficiency.
[0075] In dry mixing, the shear force generated by stirring facilitates the extension of polyvinylidene fluoride (PVDF) molecular chains and their full contact with particles, thereby improving dispersion. This is because PVDF has a long molecular chain structure, which can extend and entangle in the dry powder mixing system. When mixed with other particles, the PVDF molecular chains can coat the particle surface, forming a physical barrier. This barrier can prevent direct contact and excessive aggregation between particles, thus playing a role in dispersing the particles to a certain extent. It works synergistically with polytetrafluoroethylene (PTFE) to prevent particle agglomeration.
[0076] An appropriate amount of polyvinylidene fluoride (PVDF) can form a suitable coating layer on the particle surface, achieving a good dispersion effect. If too little is added, it cannot fully coat the particles, resulting in an unsatisfactory dispersion effect. However, if too much is added, it may cause PVDF to agglomerate, which in turn affects the dispersion of the particles and the electrochemical performance of the battery.
[0077] Step 140: The second mixture is pressed into a film using a film thinning device to obtain a positive electrode film.
[0078] Polyvinylidene fluoride (PVDF) possesses flexibility and long molecular chains. In dry processing, gaps exist between the particles of each component, easily leading to particle agglomeration and affecting the uniformity and density of the film. However, PVDF molecular chains can interweave and extend between particles, filling these gaps with their flexibility. Simultaneously, the groups on the molecular chains interact with the particle surface, preventing excessive particle aggregation and thus reducing agglomeration.
[0079] Specifically, the molecular chain of polyvinylidene fluoride contains repeating -CF2-CH2- units. The -CF2- groups in the molecular chain provide polarity, allowing the molecular chain to simultaneously adsorb the positive electrode active material, solid electrolyte, and conductive agent, forming a bridging structure of "conductive agent-positive electrode active material-conductive agent" and "solid electrolyte-positive electrode active material-solid electrolyte". This allows the positive electrode active material, solid electrolyte, and conductive agent to form a three-dimensional network structure, ensuring that the conductive agent and solid electrolyte are uniformly dispersed in the positive electrode active material. This improves the binding force between particles, reduces the gaps between particles, and enhances the film-forming properties of the membrane. In addition, the -CH2- groups in the molecular chain impart flexibility, which, during the preparation of the positive electrode membrane, allows the molecular chain to fill the gaps between the positive electrode active material, conductive agent, and solid electrolyte particles through localized chain segment deformation when under stress, providing a foundation for the stability of the subsequent membrane structure. Meanwhile, under pressure, the molecular chains in polyvinylidene fluoride align along the pressure direction to form a dynamic "flow layer," which further fills the gaps between particles and reduces particle aggregation. Because the "flow layer" can lubricate and disperse particles, it helps to improve the uniformity and stability of the film, thereby achieving good film-forming properties.
[0080] In addition, due to the synergistic effect of polar groups (-CF2-) and flexible groups (-CH2-) in the PVDF molecular chain, not only is the film-forming property of the film improved, but the film density is also achieved.
[0081] In addition, because the conductive agent and the solid electrolyte are uniformly dispersed in the positive electrode active material, they form continuous electron transport paths and ion transport channels, respectively, which reduces the resistivity of the electrode.
[0082] In dry film-forming processes, the film-forming process requires materials to possess certain plasticity and cohesive strength. The flexibility and long molecular chain structure of polyvinylidene fluoride (PVDF) endow it with good plasticity, allowing it to deform appropriately with changes in pressure and temperature during film formation. This enables the membrane materials to adhere better together. Simultaneously, the entanglement and interaction between the long molecular chains form cohesive strength, enhancing the overall strength of the membrane. Due to the addition of a solid electrolyte, these properties of PVDF help maintain structural stability, preventing the prepared membrane from cracking or delaminating during winding.
[0083] Therefore, polyvinylidene fluoride (PVDF) improves film formation, resulting in a denser and more uniform film. In batteries, resistivity is related to the material's structure and conductive pathways. A dense and uniform film structure reduces contact resistance between particles because the contact between particles is tighter, facilitating smoother electron transport. Simultaneously, the filling effect of PVDF reduces the gaps between particles, lowering the barrier to ion transport and promoting ion conduction. Thus, it reduces the battery's resistivity from both electronic and ion conduction perspectives.
[0084] Meanwhile, the fibrous three-dimensional structure formed by polytetrafluoroethylene after fiberization helps to coat the conductive agent particles and solid electrolyte and fix their distribution position, improving the stability of the dispersion of conductive agent and solid electrolyte, making them less prone to agglomeration or migration during calendering. This allows the prepared film to maintain good electronic and ion conductivity, further reducing the resistivity of the electrode sheet.
[0085] The areal density of the positive electrode film prepared in this application is 20 g / cm³. 2 -30g / cm 2 During this stage, the roll gap is 0.05mm-2mm. The required positive electrode membrane is prepared by adjusting the roll gap according to the areal density requirements of the positive electrode membrane. In this positive electrode membrane, the mass ratio of positive electrode active material, solid electrolyte, conductive agent, polytetrafluoroethylene and polyvinylidene fluoride is 84-92.5:2.5-5:3-5:1-4:1-2.
[0086] The positive electrode film provided by this invention, or the positive electrode film prepared by the method of this invention, can be used in positive electrode sheets. Specifically, the prepared positive electrode film is hot-pressed onto both sides of a carbon-coated aluminum foil to obtain a positive electrode sheet. Preferably, the hot-pressing conditions are: temperature of 100℃-150℃, pressure of 2t-30t, and roller gap of 0.1mm-4mm during the hot-pressing stage.
[0087] The method for preparing the positive electrode film provided by this invention optimizes the dry process, which not only utilizes the synergistic effect between the components to achieve a synergistic improvement in film formation effect and resistivity, but also omits steps such as coating and drying, reduces solvent use and consumption, simplifies the preparation process, significantly reduces costs, and is conducive to industrial application.
[0088] The positive electrode film of this invention can be applied to positive electrode sheets, and further to sodium-ion batteries or sodium-ion capacitors. For example, firstly, following the method described above, the positive electrode film is thermally laminated to both sides of a 12μm carbon-coated aluminum foil. After winding, the positive electrode sheet is rolled to obtain a ready-made positive electrode sheet. Then, the negative electrode sheet is prepared by mixing hard carbon negative electrode material, conductive carbon black, and polytetrafluoroethylene binder in a mass ratio of 91:2:7, using the same preparation process as the positive electrode sheet (replacing the carbon-coated aluminum foil with carbon-coated copper foil), ultimately obtaining the negative electrode sheet. Using a film cutting machine, the positive electrode sheet (44mm*62mm) and the negative electrode sheet (46mm*64mm) are sliced to produce positive and negative electrode sheets suitable for use in pouch cells. Then, the positive and negative electrode sheets are stacked together with the separator to form a core. After pre-welding the tabs, welding the tabs, baking, and ensuring the moisture content is within acceptable limits, the core is encapsulated using an aluminum-plastic film, injected with electrolyte, and sealed to form a sodium-ion cell. After encapsulation, the pouch cells undergo high-temperature aging, formation, and capacity testing to produce qualified pouch cells. The materials and methods used in the above process are commonly used in this field and will not be described in detail here.
[0089] Because the positive electrode film in this application effectively solves the problems of high resistivity and film formation of electrode plates, it improves the mechanical and conductive properties of electrode plates, thereby enhancing the overall performance of sodium-ion batteries or sodium-ion capacitors, including charging efficiency, rate performance and cycle stability, laying a solid foundation for the large-scale commercial application of sodium-ion batteries or sodium-ion capacitors.
[0090] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0091] It should be noted that, firstly, in this application, the particle size D50 of the material refers to the median particle size of the material, which can be the median value sorted by volume, mass, or quantity. In the various embodiments of this invention, the median particle size sorted by quantity is specifically used, representing the particle size of the solid electrolyte that accounts for 50% of the quantity distribution. Particle size D50 is a well-known concept in the art. The particle size D50 of the material provided in the embodiments of this invention can be determined using instruments and conventional methods known in the art. Specifically, in all embodiments of this invention, a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd. (UK) is used to determine the particle size D50.
[0092] Secondly, the ball milling in the following embodiments was carried out in a highly sealed container under conditions not exceeding 40°C and humidity not exceeding 1%.
[0093] Finally, to facilitate subsequent comparison of the resistivity of the electrode sheets in Examples 1-8 and Comparative Examples 1-2, the areal density difference between the films prepared in Examples 1-8 and Comparative Examples 1-2 was controlled to be less than 1 g / cm³ during the preparation of the positive electrode film. 2 Furthermore, Examples 1-8 and Comparative Examples 1-2 controlled the particle size D50 of the ball-milled solid electrolyte material to be between 50 nm and 200 nm by controlling the ball-to-material ratio, as well as the ball milling speed and time.
[0094] Example 1
[0095] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0096] In this embodiment, the mass ratio of NaNiO2, NaTFSI, carbon fiber, polytetrafluoroethylene, and polyvinylidene fluoride is 88:4:4:2:2.
[0097] (1) Solid electrolyte powder NaTFSI was ball-milled at a ball-to-powder ratio of 15:1 and a speed of 1000 rpm for 6 hours to obtain nanoscale solid electrolyte material.
[0098] (2) NaNiO2, ball-milled NaTFSI and carbon fiber are stirred for 20 minutes at 20°C in a high-speed shear machine at a speed of 600 rpm. The materials are dispersed and mixed evenly by mechanical force to obtain the first mixture.
[0099] (3) Under the condition of stirring at 2000 rpm at 85℃, polytetrafluoroethylene and polyvinylidene fluoride were added to the first mixture and stirred for 20 min to obtain the second mixture.
[0100] (4) The second mixture is pressed into a film with a surface density of 22.9 g / cm³ using a film-forming and thinning device. 2 The positive electrode film, its film formation process is as follows Figure 2 As shown.
[0101] (5) Under the conditions of 120℃ and 20t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0102] Example 2
[0103] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0104] In this embodiment, the mass ratio of NaNiO2, NaTFSI, carbon nanotubes, polytetrafluoroethylene, and polyvinylidene fluoride is 86:5:4:3:2.
[0105] (1) Solid electrolyte powder NaTFSI was ball-milled at a ball-to-powder ratio of 15:1 and a speed of 2000 rpm for 4 hours to obtain nanoscale solid electrolyte material.
[0106] (2) NaNiO2, ball-milled NaTFSI and carbon nanotubes were stirred for 15 minutes at 20°C in a high-speed shear machine at a speed of 500 rpm to disperse and mix the materials evenly by mechanical force to obtain the first mixture.
[0107] (3) Under the condition of stirring at 1500 rpm at 80℃, polytetrafluoroethylene and polyvinylidene fluoride were added to the first mixture and stirred for 25 min to obtain the second mixture.
[0108] (4) The second mixture is pressed into a film-forming and thinning device to a surface density of 23.2 g / cm³. 2 The positive electrode membrane.
[0109] (5) Under the conditions of 150℃ and 15t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0110] Example 3
[0111] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0112] In this embodiment, the mass ratio of NaCoO2, NaBOB, carbon nanotubes, carbon fibers, polytetrafluoroethylene, and polyvinylidene fluoride is 87.5:2.5:2.5:2.5:4:1.
[0113] (1) Solid electrolyte powder NaBOB was ball-milled at a ball-to-powder ratio of 10:1 and a speed of 2500 rpm for 5 hours to obtain nanoscale solid electrolyte material.
[0114] (2) NaCoO2, ball-milled NaBOB, carbon nanotubes, and carbon fibers were stirred for 20 minutes at 15°C in a high-speed shear machine at a speed of 400 rpm to disperse and mix the materials evenly through mechanical force, thus obtaining the first mixture.
[0115] (3) Under the condition of stirring at 3000 rpm at 80℃, polytetrafluoroethylene and polyvinylidene fluoride were added to the first mixture and stirred for 20 min to obtain the second mixture.
[0116] (4) The second mixture is pressed into a film-forming and thinning device to a surface density of 23.4 g / cm³. 2 The positive electrode membrane.
[0117] (5) Under the conditions of 100℃ and 25t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0118] Example 4
[0119] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0120] In this embodiment, the mass ratio of NaCoO2, NaBOB, NaTFS, conductive carbon black, polytetrafluoroethylene, and polyvinylidene fluoride is 91.5:1:1.5:3:1:2.
[0121] (1) Solid electrolyte powders NaBOB and NaTFS were ball-milled at a ball-to-powder ratio of 10:1 and a speed of 3000 rpm for 3 hours to obtain nanoscale solid electrolyte materials.
[0122] (2) NaCoO2, ball-milled NaBOB and NaTFS, and conductive carbon black were stirred for 25 minutes at 20°C in a high-speed shear machine at a speed of 400 rpm to disperse and mix the materials evenly through mechanical force, thus obtaining the first mixture.
[0123] (3) Under the condition of stirring at 2500 rpm at 85℃, polytetrafluoroethylene and polyvinylidene fluoride are added to the first mixture and stirred for 15 min to obtain the second mixture.
[0124] (4) The second mixture is pressed into a film-forming and thinning device to a surface density of 23.6 g / cm³. 2 The positive electrode membrane.
[0125] (5) Under the conditions of 130℃ and 20t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0126] Example 5
[0127] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0128] In this embodiment, the mass ratio of NaCoO2, NaDFOB, acetylene black, polytetrafluoroethylene, and polyvinylidene fluoride is 84-92.5:2.5-5:3-5:1-4:1-2.
[0129] (1) Solid electrolyte powder NaDFOB was ball-milled at a ball-to-powder ratio of 20:1 and a speed of 1500 rpm for 6 hours to obtain nanoscale solid electrolyte material.
[0130] (2) NaCoO2, ball-milled NaDFOB and acetylene black were stirred for 25 minutes at 15°C in a high-speed shear machine at a speed of 300 rpm to disperse and mix the materials evenly by mechanical force, thus obtaining the first mixture.
[0131] (3) Under the condition of stirring at 1000 rpm continuously at 80℃, polytetrafluoroethylene and polyvinylidene fluoride are added to the first mixture and stirred continuously for 25 min to obtain the second mixture.
[0132] (4) The second mixture is pressed into a film-forming and thinning device to a surface density of 23 g / cm³. 2 The positive electrode membrane.
[0133] (5) Under the conditions of 100℃ and 25t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0134] Example 6
[0135] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0136] In this embodiment, the mass ratio of NaNiO2, NaCoO2, NaDFOB, Ketjen black, polytetrafluoroethylene, and polyvinylidene fluoride is 50:42.5:2.5:3:1:1.
[0137] (1) Solid electrolyte powder NaDFOB was ball-milled at a ball-to-material ratio of 20:1 and a speed of 2000 rpm for 7 hours to obtain nanoscale solid electrolyte material.
[0138] (2) NaNiO2, NaCoO2, ball-milled NaDFOB and Ketjen black were stirred for 20 minutes at 20°C in a high-speed shear machine at a speed of 600 rpm to disperse and mix the materials evenly by mechanical force, thus obtaining the first mixture.
[0139] (3) Under the condition of continuous stirring at 2000 rpm at 85°C, polytetrafluoroethylene and polyvinylidene fluoride are added to the first mixture to obtain the second mixture.
[0140] (4) The second mixture is pressed into a film-forming and thinning device to a surface density of 23.3 g / cm³. 2 The positive electrode membrane.
[0141] (5) Under the conditions of 150℃ and 15t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0142] Example 7
[0143] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0144] In this embodiment, the mass ratio of NaNiO2, NaTFSI, carbon fiber, polytetrafluoroethylene, and polyvinylidene fluoride is 88:3.5:4.5:3:1.
[0145] (1) Solid electrolyte powder NaTFSI was ball-milled at a ball-to-powder ratio of 15:1 and a speed of 3000 rpm for 5 hours to obtain nanoscale solid electrolyte material.
[0146] (2) NaNiO2, ball-milled NaTFSI and carbon fiber are stirred for 15 minutes at 20°C in a high-speed shear machine at a speed of 400 rpm to disperse and mix the materials evenly by mechanical force to obtain the first mixture.
[0147] (3) Under the condition of continuous stirring at 1000 rpm at 85°C, polytetrafluoroethylene and polyvinylidene fluoride were added to the first mixture and stirred for 25 min to obtain the second mixture.
[0148] (4) The second mixture is pressed into a film with a surface density of 22.8 g / cm³ using a film-forming and thinning device. 2 The positive electrode membrane.
[0149] (5) At 140℃ and 2t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0150] Example 8
[0151] In this embodiment of the invention, a positive electrode film was prepared and then fabricated into a positive electrode sheet.
[0152] In this embodiment, the mass ratio of NaNiO2, NaTFSI, carbon nanotubes, polytetrafluoroethylene, and polyvinylidene fluoride is 85:4:5:4:2.
[0153] (1) Solid electrolyte powder NaTFSI was ball-milled at a ball-to-powder ratio of 20:1 and a speed of 2000 rpm for 4 hours to obtain nanoscale solid electrolyte material.
[0154] (2) NaNiO2, NaTFSI and carbon nanotubes were stirred for 15 minutes at 20°C in a high-speed shear machine at a speed of 700 rpm to disperse and mix the materials evenly by mechanical force, thus obtaining the first mixture.
[0155] (3) Under the condition of stirring continuously at 1500 rpm at 80℃, polytetrafluoroethylene and polyvinylidene fluoride are added to the first mixture and stirred continuously for 20 min to obtain the second mixture.
[0156] (4) The second mixture is pressed into a film-forming and thinning device to a surface density of 23.4 g / cm³. 2 The positive electrode membrane.
[0157] (5) Under the conditions of 100℃ and 30t, the positive electrode film is hot-pressed onto both sides of the carbon-coated aluminum foil to obtain the positive electrode sheet.
[0158] Comparative Example 1
[0159] A positive electrode film was prepared in this comparative example and then fabricated as a positive electrode sheet.
[0160] The difference between Comparative Example 1 and Example 1 is that NaTFSI and polyvinylidene fluoride are not added in Comparative Example 1.
[0161] The film formation process in Comparative Example 1 is as follows: Figure 3 As shown, the areal density of the finally prepared positive electrode film is 22.9 g / cm³. 2 .
[0162] Comparative Example 2
[0163] A positive electrode film was prepared in this comparative example and then fabricated as a positive electrode sheet.
[0164] The difference between Comparative Example 2 and Example 1 is that no polyvinylidene fluoride was added in Comparative Example 2.
[0165] The film formation process in Comparative Example 2 is as follows: Figure 4 As shown, the areal density of the finally prepared positive electrode film is 22.8 g / cm³. 2 .
[0166] The performance of the positive electrode sheets prepared in the above embodiments and comparative examples was characterized.
[0167] The areal density, compaction density, and resistivity of the electrode sheets prepared in the above embodiments and comparative examples were tested, and the measured data are listed in Table 1.
[0168] The areal density test method and operation steps are as follows:
[0169] 1. Use a circular die to cut the positive electrode sheet, ensuring an area of 10 cm². 2 The error shall not exceed ±0.5cm 2 , to be used as samples for testing.
[0170] 2. Weigh the sample to be tested using a precision balance (accuracy 0.1 mg).
[0171] Calculate the areal density using the following formula:
[0172] Areal density = electrode mass / membrane area.
[0173] The compaction density test method and operation steps are as follows:
[0174] 1. Use a circular die to cut the positive electrode sheet, ensuring an area of 10 cm². 2 The error shall not exceed ±0.5cm 2 , to be used as samples for testing.
[0175] 2. Measure the thickness of the sample to be tested using a micrometer, and weigh the sample using a precision balance (accuracy 0.1 mg).
[0176] Calculate compaction density using the following formula:
[0177] Compacted density = Electrode mass / Electrode area * Electrode thickness.
[0178] It should be noted that the test methods for the areal density of the diaphragm in each embodiment are the same as the test methods for the areal density of the electrode sheet.
[0179] The resistivity testing method and operation steps are as follows:
[0180] 1. Sample cutting:
[0181] Use a circular die to cut the electrode sheets, ensuring an area of 10 cm². 2 The error shall not exceed ±0.5cm 2 , to be used as samples for testing.
[0182] 2. Testing: Place the sample to be tested on the metal terminals of the resistivity meter. Apply a pressure of 5 MPa to both sides of the sample using the upper metal terminals and maintain the pressure for 5 seconds. Click "Start Resistivity Test" to measure the resistance R and thickness d. Calculate the resistivity using the following formula:
[0183] ρ = R·A / d, where R is the measured resistance value, A is the contact area, i.e. the area of the sample to be tested, and d is the thickness of the electrode sheet.
[0184] The measured thickness d is actually the sum of the thicknesses of the positive electrode film and the aluminum foil. Therefore, the method for measuring the thickness of the positive electrode film prepared in the examples and comparative examples is: d minus half the difference in thickness between the positive electrode film and the aluminum foil. In this application, the aluminum foil used is a conventional 12μm foil with an areal density of 3.5g / cm³. 2 .
[0185] Example <![CDATA[Compaction density (g / cm 3 )]]> <![CDATA[Areal density (g / cm 2 )]]> Electrode resistivity (Ω*cm) Example 1 2.80 49.3 1.1 Example 2 2.75 49.9 1.0 Example 3 2.82 50.3 1.3 Example 4 2.70 50.7 0.9 Example 5 2.80 49.5 0.7 Example 6 2.82 50.1 0.5 Example 7 2.75 49.1 1.1 Example 8 2.81 50.3 1.2 Comparative Example 1 2.79 49.3 3.8 Comparative Example 2 2.80 49.1 Failed to form film
[0186] Table 1
[0187] Figure 2 This is the film-forming process of Example 1. Figure 3The film-forming process of Comparative Example 1 is different from that of Example 1. In Comparative Example 1, no solid electrolyte and polyvinylidene fluoride were added to the components for preparing the positive electrode film. This shows that the positive electrode film prepared by either conventional process or the preparation method provided by the present invention can be successfully rolled up.
[0188] Figure 4 The film-forming process of Comparative Example 2 differs from Example 1 in that Comparative Example 2 did not include polyvinylidene fluoride (PVDF) in the components used to prepare the positive electrode membrane. As shown in the figure, the membrane edges were severely damaged and could not be rolled up smoothly. This indicates that simply adding a solid electrolyte does not guarantee successful film formation compared to conventional positive electrode membrane preparation processes. However, the addition of both solid electrolyte and PVDF allows for successful film formation. This is because the flexibility and long molecular chain structure of PVDF endow it with good plasticity, enabling it to deform appropriately with changes in pressure and temperature during film formation, allowing the membrane materials to adhere better. Simultaneously, the entanglement and interaction between the long molecular chains create cohesion, enhancing the overall strength of the membrane. The addition of the solid electrolyte, combined with these properties of PVDF, helps maintain structural stability, preventing the prepared membrane from cracking or delaminating during winding.
[0189] According to Table 1, a comparison of the areal density, compaction density, and electrode resistivity between Examples 1-8 and Comparative Example 1 shows that, under the premise that the areal density of the prepared films is not significantly different, their compaction densities are also not significantly different. Applying the preparation method of this invention, by adding solid electrolyte and polyvinylidene fluoride to the components for preparing the positive electrode film, significantly reduces the resistivity of the electrode. This is because polyvinylidene fluoride has flexible and long molecular chains, which can interweave and extend between particles, filling these gaps using its flexibility. Simultaneously, the groups on the molecular chains interact with the particle surface, preventing excessive aggregation between particles, thereby reducing the occurrence of agglomeration. This not only reduces the resistivity of the electrode but also improves its film-forming properties. Specific analysis is as follows:
[0190] On the one hand, during processing, polytetrafluoroethylene (PTFE) undergoes fibrosis, forming nanofibers. These nanofibers interact with the positive electrode active material, solid electrolyte, and conductive agent, creating a three-dimensional fibrous structure. The conductive agent and solid electrolyte are uniformly dispersed within this fibrous three-dimensional structure, forming continuous electron transport paths and ion transport channels, thus reducing the electrode's resistivity. On the other hand, the PTFE molecular chain contains repeating -CF2-CH2- units. The -CF2- groups in the molecular chain provide polarity, allowing the molecular chain to simultaneously adsorb the positive electrode active material, solid electrolyte, and conductive agent. This forms a bridging structure between "conductive agent-positive electrode active material-conductive agent" and "solid electrolyte-positive electrode active material-solid electrolyte," enabling the positive electrode active material, solid electrolyte, and conductive agent to form a... The three-dimensional network structure allows the conductive agent and solid electrolyte to be uniformly dispersed in the positive electrode active material, forming continuous electron transport paths and ion transport channels, respectively, further reducing the resistivity of the electrode. On the other hand, the -CH2- groups in the polyvinylidene fluoride (PVDF) molecular chain endow the molecular chain with flexibility. During the preparation of the positive electrode film, under stress, the molecular chain fills the gaps between particles through local segment deformation. At the same time, the molecular chains in PVDF are oriented along the pressure direction to form a dynamic "flow layer" that fills the gaps between particles and reduces particle aggregation. The local segment deformation provides the basis for the formation of the "flow layer". Through the synergistic effect of local segment deformation and the "flow layer", the positive electrode film maintains the uniformity and stability of the structure during the forming process, thus achieving film-forming properties.
[0191] The positive electrode film utilizes the synergistic effect between its components to achieve a synergistic improvement in film formation and resistivity. The excellent film formation effect ensures the structural stability and consistency of the positive electrode sheet, providing a foundation for the long-term stable operation of the battery. Meanwhile, the lower resistivity improves the battery's charge and discharge efficiency, reduces energy loss, and helps to improve the overall performance of the battery. These comprehensive performance improvements give sodium-ion batteries using the positive electrode film prepared by this invention a greater advantage in the market and enable them to meet the battery performance requirements of more application scenarios.
[0192] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A positive electrode membrane, characterized in that, The positive electrode membrane comprises a positive electrode active material, a solid electrolyte, a conductive agent, polytetrafluoroethylene, and polyvinylidene fluoride in a mass ratio of 84-92.5:2.5-5:3-5:1-4:1-2; During processing, the polytetrafluoroethylene undergoes fibrosis to form nanofibers. These nanofibers interact with the positive electrode active material, the solid electrolyte, and the conductive agent through van der Waals forces, forming a physical encapsulation. Through the interweaving of the nanofibers, the positive electrode active material, the solid electrolyte, and the conductive agent are "woven" into a fibrous three-dimensional structure. This allows the conductive agent and the solid electrolyte to be uniformly dispersed in the fibrous three-dimensional structure, forming continuous electron transport paths and ion transport channels, respectively, thereby reducing the resistivity of the electrode. The polyvinylidene fluoride (PVDF) molecular chain contains -CF2-CH2- repeating units, wherein the -CF2- groups in the molecular chain provide polarity, allowing the molecular chain to simultaneously adsorb the positive electrode active material, the solid electrolyte, and the conductive agent, forming a bridging structure of "conductive agent-positive electrode active material-conductive agent" and "solid electrolyte-positive electrode active material-solid electrolyte". This allows the positive electrode active material, the solid electrolyte, and the conductive agent to form a three-dimensional network structure, enabling the conductive agent and the solid electrolyte to be uniformly dispersed in the positive electrode active material, forming continuous electron transport paths and ion transport channels, respectively, further reducing the resistivity of the electrode.
2. The positive electrode film according to claim 1, characterized in that, The -CH2- groups in the polyvinylidene fluoride (PVDF) molecular chain impart flexibility to the chain. During the preparation of the positive electrode membrane, the molecular chain undergoes local segment deformation to fill the gaps between the positive electrode active material, the conductive agent, and the solid electrolyte particles. Simultaneously, under pressure, the molecular chain aligns along the pressure direction to form a dynamic "flow layer," filling the gaps between particles and reducing particle aggregation. Local segment deformation provides the basis for the formation of the "flow layer." Through the synergistic effect of local segment deformation and the "flow layer," the positive electrode membrane maintains structural uniformity and stability during the forming process, thereby achieving film-forming properties.
3. The positive electrode film according to claim 1, characterized in that, The positive electrode active material is a layered transition metal oxide, including one or more of NaCoO2 and NaNiO2; The solid electrolyte includes one or more of sodium bis(oxalateborate), sodium bis(trifluoromethanesulfonylimide), and sodium difluorooxalateborate. The conductive agent includes one or more of carbon nanotubes, conductive carbon black, Ketjen black, carbon fiber, and acetylene black.
4. A method for preparing a positive electrode film according to any one of claims 1-3, characterized in that, The preparation method includes: Solid electrolyte powder was ball-milled to obtain nanoscale solid electrolyte materials; The positive electrode active material, the solid electrolyte material, and the conductive agent are mixed evenly in a high-speed shearing machine to obtain a first mixture; While maintaining stirring at 80℃-85℃, polytetrafluoroethylene and polyvinylidene fluoride are added to the first mixture, causing the polytetrafluoroethylene to fibrose under shear force and temperature, resulting in a second mixture with a fibrous three-dimensional structure. The second mixture is pressed into a film using a film-forming and thinning device to obtain a positive electrode film; In the positive electrode membrane, the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent, the polytetrafluoroethylene, and the polyvinylidene fluoride is 84-92.5:2.5-5:3-5:1-4:1-2.
5. The preparation method according to claim 4, wherein the positive electrode active material is a layered transition metal oxide, including one or more of NaCoO2 and NaNiO2; The solid electrolyte includes one or more of sodium bis(oxalateborate), sodium bis(trifluoromethanesulfonylimide), and sodium difluorooxalateborate. The conductive agent includes one or more of carbon nanotubes, conductive carbon black, Ketjen black, carbon fiber, and acetylene black.
6. The preparation method according to claim 4, characterized in that, The ball milling speed is 1000rpm-3000rpm, and the ball milling time is 3h-7h.
7. The preparation method according to claim 4, characterized in that, When preparing the first mixture, the high-speed shear machine rotates at 300 rpm to 700 rpm, the time is 15 min to 25 min, and the temperature is 15℃ to 20℃.
8. The preparation method according to claim 4, characterized in that, During fiberization, the high-speed shearing machine rotates at 1000 rpm to 3000 rpm for 15 min to 25 min.
9. A positive electrode sheet, characterized in that, The positive electrode sheet includes the positive electrode film as described in any one of claims 1-3, or the positive electrode film prepared by the preparation method as described in any one of claims 4-8.
10. An energy storage device, characterized in that, The energy storage device includes: a sodium-ion battery or a sodium-ion capacitor; The energy storage device includes the positive electrode film according to any one of claims 1-3, or the positive electrode film prepared by any one of claims 4-8, or the positive electrode sheet according to claim 9.